The secret at Shadow Ranch - Keene, Carolyn (Keene, Carolyn. Nancy Drew mystery stories ;, 1931)
Nancy arrives in Phoenix, Arizona, eagerly looking forward to a fun-filled vacation at Shadow Ranch but finds herself embroiled in a baffling mystery involving a phantom horse and buried treasure. Local people believe that the ghostly animal is carring out the curse of Dirk Valentine, the romantic outlaw who was killed many years ago at Shadow Ranch, where he had gone to fulfill a promise to his sweetheart ...